Experimental Study on Internal Erosion of Granite Weathered Soil Under Dynamic Head Action - Hao WANG; Gengming YAN; Chuandong LI; Yingying HUANG; Zhichao ZHANG (工程科学与技术)
Objective The granite weathering process, influenced by internal and external forces from various geological effects, the distribution of irregular joints, and other factors, causes the granite weathering shell to exhibit differential weathering. This results in the formation of a granite binary structure of slopes, with the upper part of the slope consisting of weathered soil and the lower part of weathered rock and discontinuous differences between the upper and lower parts at the weathering interface. Weathered soil is the main source of granite binary-structured slopes, and clarification of its internal erosion characteristics is the basis for studying the damage mode and slip promotion mechanism of this type of slope. The internal erosion of granite-weathered soil under groundwater seepage involves fine particle migration and siltation. Due to the non-homogeneity of granite-weathered soil and the randomness of particle migration, existing studies cannot fully reveal the internal erosion process and particle migration law of granite-weathered soil. Additionally, there are fewer studies on the interaction process between fine particle transport and pore plugging inside the soil under dynamic head conditions, which limits further understanding of particle migration and internal erosion processes in granite-weathered soil.Methods This study focuses on the granite slope next to County Road X135 in Huangqi Town, Lianjiang County, Fujian Province. Understanding the geological phenomena of internal erosion in weathered soil clarifies the environment and triggering factors of internal erosion in granite-weathered soil. A lateral seepage test is conducted using a sandbox, combined with discrete element numerical simulations to reproduce the evolution of the internal erosion process. This reveals the dynamic processes of fine particle migration and siltation, investigates the influence of hydraulic conditions on internal erosion development, and summarizes the mechanisms of internal erosion in granite-weathered soil.Results and Discussions The results show that soil erosion is a gradual development process. In the initial stage of seepage, the bonding of fine particles at weak points in the soil is weak, making them highly susceptible to loss under water flow. Over time, the soil gradually stabilizes, and water flow preferentially follows established seepage channels. From a macroscopic perspective, more active water movement results in more developed seepage pore channels. At a finer scale, fine particle migration during erosion is irregular, expanding the pore structure while also causing blockages or deposition at the bedrock interface. Under dynamic head actions, fine particles continue to migrate, forming pore cavities within the soil, which eventually connect to form seepage channels, accelerating water transport. Increasing the amplitude of head change and the seepage inclination angle induces greater soil particle migration and loss, exacerbating internal erosion and prolonging the stabilization time of the soil. The composition and proportion of lost particles in weak zones are very similar to those of the upper weathered soil, indicating that the weak zones form through fine particle migration and deposition under seepage effects. This self-filtering process reflects the dynamic interaction of particle migration and deposition in granite weathered soil.Conclusions Under long-term rainfall, the fully weathered, fine-grained clay particles in granite weathered soil aggregate at different weathering interfaces. The long-term softening effect of groundwater forms weak structural surfaces that control slope stability. These weak structural surfaces divide the slope into an upper layer of granite weathered soil and a lower layer of strongly weathered granite, forming a binary structure. During the self-filtering process, the coarsening of soil particles caused by fine particle migration easily triggers soil collapse and damage. Additionally, the softening of the base-cover interface due to fine particle deposition evolves into a critical factor controlling slope stability. These factors are the primary causes of instability in granite binary-structured slopes. This study preliminarily clarifies the mechanisms of internal erosion in granite weathered soil and provides a theoretical basis for predicting slope instability and implementing disaster prevention and mitigation measures for granite slopes.